Transparent hybrid anapole metasurfaces with negligible electromagnetic coupling for phase engineering - Kuznetsov Alexey V.; Canós Valero Adrià; Tarkhov Mikhail; Bobrovs Vjaceslavs; Redka Dmitrii; Shalin Alexander S. (Nanophotonics, 2021)
All-dielectric nanophotonics has become one of the most active fields of research in modern optics, largely due to the opportunities offered by the simultaneous resonant control of electric and magnetic components of light at the nanoscale. In this rapidly evolving scenario, the possibility to design artificial Huygens sources by overlapping electric and magnetic resonances has established a new paradigm in flat optics, bringing devices closer to efficient wavefront shaping with direct phase engineering at the level of the individual meta-atoms. However, their efficiency is fundamentally limited by the near-field coupling between the constituents of the metalattice. In this work, we challenge this well-conceived notion and propose an alternative concept to achieve phase control and full transmission in metasurfaces, based on the unusual properties of the nonradiating sources known as hybrid anapoles (HAs). We analyze theoretically an array of such sources and demonstrate that HAs are characterized by negligible coupling with their neighbors. Therefore, in contrast to Huygens particles, the proposed sources can operate as individual meta-atoms even in highly compact designs, becoming robust against strong disorder and preserving its characteristics when deposited on dielectric substrates. Remarkably, the phase of the transmitted wave can be modulated with negligible reflection. To illustrate the capabilities of our platform, we also utilize a disordered HA array to implement a controlled phase modulation to an ultrafast Gaussian pulse. The results of our study represent a departure from the currently established designs and open an avenue toward the realization of new devices for flat optics with unprecedented efficiency.